Probing third-generation New Physics with K→πνν¯ and B→K(⁎)νν¯ - L. Allwicher; M. Bordone; G. Isidori; G. Piazza; A. Stanzione (Physics Letters B)
The recent observation of the K+→π+νν¯ decay by NA62 is an important milestone in precision flavor physics. Together with evidence of B+→K+νν¯ reported by Belle-II, they are the only FCNC decays involving third-family leptons where a precision close to the SM expectation has been reached. We study the implications of these recent results in the context of a new physics scenario aligned to the third generation, with an approximate U(2)5 flavor symmetry acting on the light families. We find that the slight excess observed in both channels supports the hypothesis of non-standard TeV dynamics of this type, as also hinted at by other B-meson decays, consistently with bounds from colliders and electroweak observables. We further discuss how future improvements in precision could affect this picture, highlighting the discovery potential in these di-neutrino modes.